The Influence of Transformational Leadership Style and Work Discipline on Employee Performance With Work Motivation as a Mediation Variable - Riyo Adi Sanjaya; Dewi Susita; Puji Wahono (International Journal of Educational and Life Sciences, 2024)
The aim of this research is to comprehensively describe and explain the influence of transformational leadership style and work discipline on employee performance through the mediation of work motivation. This research was conducted at Harum Manis Roti dan Kue with a sample size of 120 employees. This research method uses a quantitative research survey method, while analyzing the data uses path analysis. Data collection was carried out through filling out questionnaires. Based on the calculation results, a path analysis was obtained: 1) transformational and disciplined leadership styles influence employee performance 2) work motivation also influences performance, 3) transformational leadership style has a positive influence on employee performance, 4) work discipline has a negative influence on employee performance, 5) leadership style positive effect on work motivation, 6) work discipline has a positive effect on work motivation, 7) work motivation has a negative effect on employee work performance, 8) work motivation is able to mediate the positive effect of transformational leadership style on employee performance, 9) work motivation is able to mediate work discipline has a positive effect on employee performance, transformational and disciplined leadership styles influence employee performance with an R2 value of 0.364 (weak) or 36.4% while 54.6% is influenced by other variables.